Organocatalytic asymmetric mannich, formal [4+1] and [4+2] annulation reactions - Shi, Zugui (2012)
In this doctoral thesis, the research work that was carried out during the last four years will be divided into 5 chapters. Firstly, an introduction to the field of organocatalysis will be described in chapter 1. This will be followed by the first example of an organocatalytic asymmetric Mannich reaction of α-isothiocynamide with tosyl imines. This methodology leads to the facile synthesis of protected α, β-diamino acid derivatives with excellent diastereo- and enantioselectivities. A simple quinine derivative was proven to be an efficient catalyst to promote this reaction, and only low catalyst loading (2.5 mmol%) was required. A wide substrate scope, involving aromatic and aliphatic aldehydes derived imines, was well tolerated. Isoxazoline N-oxides are intriguing synthetic targets as they can be readily converted into highly functionalized γ-hydroxy-α-amino acids or γ-amino-α-hydroxy acids. In chapter 3, a novel methodology for the preparation of optically active cis-isoxazoline N-oxides developed via a formal [4+1] annulation reaction of α-Iodoaldehydes with 2-nitroacyrates, in the presence of (S)-diphenyl trimethylsilyl ether pyrrolidine will be discussed. Additionally, a concise synthesis of chiral densely functionalized α-amino lactone from the isoxazoline N-oxide product will be demonstrated. In chapter 4, a new [4+2] annulation reaction of vinyl ketones with N-sulfonyl-1-aza-1, 3-dienes, using PPh3 as catalyst, will be presented. Phenol additives were found to improve reaction rates and diastereoselectivities. This protocol established a practical process to the preparation of highly substituted tetrahydropyridines, in good to excellent yields and diastereoselectivities, with broad substrates scope. Lastly, in chapter 5, the asymmetric version of this [4+2] annulation reaction was realized by chiral phosphines derived from amino acids. Good yields, moderate to good diastereo- and enantioselectivities were obtained. In addition, benzensulfonamide was proven to be effective in improving enantioselectivity.